The Role of Plasma Membrane Sodium/Hydrogen Exchangers in Gastrointestinal Functions: Proliferation and Differentiation, Fluid/Electrolyte Transport and Barrier Integrity - Nikolovska, Katerina; Seidler, Ursula E.; Stock, Christian (Frontiers in Physiology, 2022)
The five plasma membrane Na+/H+ exchanger (NHE) isoforms in the gastrointestinal tract are characterized by distinct cellular localization, tissue distribution, inhibitor sensitivities, and physiological regulation. NHE1 (Slc9a1) is ubiquitously expressed along the gastrointestinal tract at the basolateral membrane of enterocytes, but so far, an exclusive role for NHE1 in enterocyte physiology has remained elusive. NHE2 (Slc9a2) and NHE8 (Slc9a8) are apically expressed isoforms with ubiquitous distribution along the colonic crypt axis. They are involved in pHi regulation of intestinal epithelial cells. Combined use of a knockout mouse model, intestinal organoid technology, and specific inhibitors revealed previously unrecognized actions of NHE2 and NHE8 in enterocyte proliferation and differentiation. NHE3 (Slc9a3), expressed in the apical membrane of differentiated intestinal epithelial cells, functions as the predominant nutrient-independent Na+ absorptive mechanism in the gut. The new selective NHE3 inhibitor (Tenapanor) allowed discovery of novel pathophysiological and drug-targetable NHE3 functions in cystic-fibrosis associated intestinal obstructions. NHE4, expressed in the basolateral membrane of parietal cells, is essential for parietal cell integrity and acid secretory function, through its role in cell volume regulation. This review focuses on the expression, regulation and activity of the five plasma membrane Na+/H+ exchangers in the gastrointestinal tract, emphasizing their role in maintaining intestinal homeostasis, or their impact on disease pathogenesis. We point to major open questions in identifying NHE interacting partners in central cellular pathways and processes and the necessity of determining their physiological role in a system where their endogenous expression/activity is maintained, such as organoids derived from different parts of the gastrointestinal tract.